Thermal–statistical odd–even fermions’ staggering effect and the order–disorder disjunction - Pennini, Flavia Catalina (2021)
We review thermal–statistical considerations on the odd–even staggering effect (OES) in fermions. There is a well known OES in nuclear binding energies at zero temperature. We discuss here a thermal OES (finite temperatures) that establishes links with the order–disorder disjunction. The present thermal considerations cannot be found in the nuclear literature.